SUMO enters the ring: the emerging role of SUMOylation in Magnaporthe oryzae pathogenicity. Issue 3 (12th July 2018) - Littlejohn, George R.
Abstract : This article is a Commentary on Liu et al., 219 : 1031–1047 .